2013
DOI: 10.1128/iai.00552-13
|View full text |Cite|
|
Sign up to set email alerts
|

Poison Domains Block Transit of Translocated Substrates via the Legionella pneumophila Icm/Dot System

Abstract: Legionella pneumophila uses the Icm/Dot type 4B secretion system (T4BSS) to deliver translocated protein substrates to the host cell, promoting replication vacuole formation. The conformational state of the translocated substrates within the bacterial cell is unknown, so we sought to determine if folded substrates could be translocated via this system. Fusions of L. pneumophila Icm/ Dot-translocated substrates (IDTS) to dihydrofolate reductase (DHFR) or ubiquitin (Ub), small proteins known to fold rapidly, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…The reason for this difference in amino acid profile between effectors and noneffectors is currently not known, but a possible explanation is that the requirement of effectors to unfold during translocation by the Icm/Dot transporter (66) and to refold with their C-terminal ends exposed generated evolutionary constraints that affect the amino acid composition of the effector proteins. The newly identified C. burnetii effectors are expressed during infection.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this difference in amino acid profile between effectors and noneffectors is currently not known, but a possible explanation is that the requirement of effectors to unfold during translocation by the Icm/Dot transporter (66) and to refold with their C-terminal ends exposed generated evolutionary constraints that affect the amino acid composition of the effector proteins. The newly identified C. burnetii effectors are expressed during infection.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that in bacteriological medium, the Lpg2149 expression only becomes detectable in the early exponential phase, suggesting that it functions when the bacteria began to replicate 40 . Because proteins being translocated by the Dot/Icm system are in their unfolded forms 46 , Lpg2149 may inhibit the activity of MavC and MvcA by preventing their translocation through forming protein complexes in bacterial cells or by blocking the activity of translocated proteins in host cells. Yet, the exact time and the extent of its inhibition of MavC and MvcA still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…As many effectors seem to be of low abundancy, several assays employ overexpression and exploit that the T4SS tolerates reporter domains fused to the N-terminus of effectors, if these do not fold rapidly into rigid structures (Amyot et al, 2013 ). One or multiple epitope tags [e.g., M45 (Weber et al, 2006 ), 4xHemagglutinin (HA) (Dolezal et al, 2012 ), 13xMyc (Viner et al, 2012 ) or 3xFlag (Isaac et al, 2015 )] were employed to detect translocated effectors.…”
Section: Probing Translocation and Localizationmentioning
confidence: 99%